Dual action of bacteriocin PLNC8 αβ through inhibition of Porphyromonas gingivalis infection and promotion of cell proliferation. Issue 5 (12th June 2017) - Bengtsson, Torbjörn; Zhang, Boxi; Selegård, Robert; Wiman, Emanuel; Aili, Daniel; Khalaf, Hazem
Abstract: Periodontitis is a chronic inflammatory disease that is characterised by accumulation of pathogenic bacteria, including Porphyromonas gingivalis, in periodontal pockets. The lack of effective treatments has emphasised in an intense search for alternative methods to prevent bacterial colonisation and disease progression. Bacteriocins are bacterially produced antimicrobial peptides gaining increased consideration as alternatives to traditional antibiotics. We show rapid permeabilisation and aggregation of P. gingivalis by the two-peptide bacteriocin PLNC8 αβ. In a cell culture model, P. gingivalis was cytotoxic against gingival fibroblasts. The proteome profile of fibroblasts is severely affected by P. gingivalis, including induction of the ubiquitin-proteasome pathway. PLNC8 αβ enhanced the expression of growth factors and promoted cell proliferation, and suppressed proteins associated with apoptosis. PLNC8 αβ efficiently counteracted P. gingivalis -mediated cytotoxicity, increased expression of a large number of proteins and restored the levels of inflammatory mediators. In conclusion, we show that bacteriocin PLNC8 αβ displays dual effects by acting as a potent antimicrobial agent killing P. gingivalis and as a stimulatory factor promoting cell proliferation. We suggest preventive and therapeutical applications of PLNC8 αβ in periodontitis to supplement the host immune defence against P. gingivalis infection and support wound healing processes. Abstract : The two-peptide bacteriocin PLNC8 αβ lyses the periodontal pathogen Porphyromonas gingivalis, and suppresses P. gingivalis -mediated cytotoxicity and accumulation of inflammatory mediators from gingival fibroblasts.